Empowering Communities through Digitalization and Marketing: A Community Service Initiative in Pematang Johar Village - Sri Rezeki; Leylawati Joremi; Kahfi Puddin; Aprinawati Aprinawati; Fides Del Castillo; Apriyansyah Sipayung; Fadillah Fasha (Eastasouth Journal of Positive Community Services, 2025)
Community empowerment through digital literacy has become increasingly important, especially for Micro, Small, and Medium Enterprises (MSMEs) that serve as the backbone of Indonesia’s rural economy. This community service project, conducted in Pematang Johar Village, Deli Serdang Regency, aimed to strengthen the capacity of local MSMEs in implementing digital marketing strategies to improve product visibility and tourism potential. The activity was part of an international collaboration between several universities from Indonesia and Malaysia. The method used combined education, training, and mentoring, focusing on practical use of social media and online branding. Results showed that participants were able to create promotional content, manage social media pages, and integrate local tourism themes into their business promotion. The program encouraged MSMEs to adopt a digital mindset and positioned Pematang Johar as a community ready to develop sustainable digital tourism.